ETIKA BISNIS ISLAM: IMPLEMENTASI PADA KELOMPOK KEWIRAUSAHAAN MAHASISWA PRODI EKONOMI SYARIAH ZA GABIN DI UNIVERSITAS ISLAM NEGERI SURABAYA - Moh. Nasirul Haq Sayuti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The student entrepreneurship group from the Sharia Economics Program at the State Islamic University of Surabaya produces “layered gabin” as their main product. Students in this group are focused on learning Islamic economics. This research utilizes a phenomenological approach in field research, with data collection methods including observation, interviews, and documentation. The data is then analyzed using qualitative descriptive analysis. The results of this study indicate that the student entrepreneurship group from the Sharia Economics Program applies Islamic business ethics by prioritizing honesty, fairness, promisekeeping, and cleanliness in the production process.